The Linguistic History of the Emergence of the Syntactic dispute - Al-Adamat, Bassam Awwad (Journal of Arabic Language Sciences and Literature, 2022)
This study investigates the linguistic history of the emergence or the syntactic dispute. It indicates the result of that history reaching linguistic texts sincerity. This paper links them to social, historical and cultural events related to conditions on the one hand, and to scholars who form an important role on the other one. The study consists of several sections such as introduction. Firstly, the researcher addresses linguistic history of grammatical disagreement's observations. Secondly, he investigates history through grammatical difference's beginning. Thirdly, he addresses history of Kufian's term in AlKitab for Sibawayh. Fourthly, he addresses grammatical disagreement's maturity and its schools emergence and finally, he addresses many grammatical disagreement's models.
Keywords: Grammatical disagreement; Kufian; Disagreement issue